Quinoa in Peru: Andean Pseudocereal, a food for present and future generations - Jesús De La Cruz-Arango (Journal of the Selva Andina Biosphere)
Quinoa (Chenopodium quinoa), an Andean crop of importance for its high nutritional value, contains essential amino acids, trace elements, vitamins, fiber that our body requires, in addition to being gluten-free. Even superior to other cereals such as wheat, barley and soybeans, only comparable to milk protein. It has valuable therapeutic properties and other benefits1,2. In fact, it is a gift from our ancestors, inherited from the pre-Incas and Incas. A species protected and preserved by the indigenous populations of South America as food for present and future generations2. However, during the Spanish conquest and the colonial and even republican era in Peru, it was marginalized and despised, considered Indian food and excluded from the table of wealthy families. Over the centuries, it faced numerous challenges, including attempts to erase its spiritual significance during colonization3. Despite this, Andean peoples have maintained and used it as a valuable food, even with its difficulties in harvesting and eliminating its bitterness due to the presence of saponins4.